Multimodal approach for oral rehabilitation in an irradiated head and neck patient: a case report (Research, Society and Development, 2020)
The present study aimed to report a clinical case of a multimodal approach for the oral rehabilitation of a 69-year-old male patient who received radiotherapy in the head and neck (3D-conformal, total radiation dose 70Gy) for larynx metastasis from bowel cancer. At the first dental appointment, the patient complained of missing teeth and dry mouth. In addition, radiation caries lesions were observed in most teeth, which also exhibited extensive coronary destruction. The treatment planning consisted of oral environment adequacy by non-surgical periodontal therapy (tooth scaling and root planning) and extraction of tooth #27 with the aid of antimicrobial photodynamic therapy for healing improvement. Following, endodontic treatment with subsequent decoronated of unrestorable roots and crown restorations were performed, as well as rehabilitation with removable partial dentures later. The dental management of post-irradiated patients in the head and neck must be carefully planned and conducted by an interdisciplinary dental team, considering the serious consequences resulting from the deleterious effects of radiotherapy in the oral cavity. As such, the negative impact of radiotherapy on the patients’ quality of life may be mitigated.